Pain-causing stinging nettle toxins target TMEM233 to modulate NaV1.7 function - Sina Jami; Jennifer R. Deuis; Tabea Klasfauseweh; Xiaoyang Cheng; Sergey Kurdyukov; Felicity Chung; Andrei L. Okorokov; Shengnan Li; Jiangtao Zhang; Ben Cristofori-Armstrong; Mathilde R. Israel; Robert J. Ju; et al. (Nature Communications, 2023)
Abstract Voltage-gated sodium (NaV) channels are critical regulators of neuronal excitability and are targeted by many toxins that directly interact with the pore-forming α subunit, typically via extracellular loops of the voltage-sensing domains, or residues forming part of the pore domain. Excelsatoxin A (ExTxA), a pain-causing knottin peptide from the Australian stinging tree Dendrocnide excelsa, is the first reported plant-derived NaV channel modulating peptide toxin. Here we show that TMEM233, a member of the dispanin family of transmembrane proteins expressed in sensory neurons, is essential for pharmacological activity of ExTxA at NaV channels, and that co-expression of TMEM233 modulates the gating properties of NaV1.7. These findings identify TMEM233 as a previously unknown NaV1.7-interacting protein, position TMEM233 and the dispanins as accessory proteins that are indispensable for toxin-mediated effects on NaV channel gating, and provide important insights into the function of NaV channels in sensory neurons.